2014
DOI: 10.1063/1.4898363
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of energy-saving behavioral intention among residents in Beijing: Extending the theory of planned behavior

Abstract: Given the rapid increase of residential energy consumption in Beijing, the question of how to promote residential energy-saving behavior is an emerging topic that is increasingly engaging the attention of scholars. To address this issue, this paper provides an empirical analysis that identifies and explores the determinants of an energy-saving behavioral intention among residents from the perspective of the theory of planned behavior (TPB). A theoretical model was constructed by refining and extending the clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
110
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(131 citation statements)
references
References 45 publications
(67 reference statements)
18
110
3
Order By: Relevance
“…Namely, Behavioural intention (Thøgersen and Grønhøj, and Wang et al . (); Attitude (Botetzagias et al . (, Abrahamse and Steg, 2011 and Thøgersen and Grønhøj, 2010); Subjective norm (Ajzen et al .…”
Section: Methodsmentioning
confidence: 95%
See 2 more Smart Citations
“…Namely, Behavioural intention (Thøgersen and Grønhøj, and Wang et al . (); Attitude (Botetzagias et al . (, Abrahamse and Steg, 2011 and Thøgersen and Grønhøj, 2010); Subjective norm (Ajzen et al .…”
Section: Methodsmentioning
confidence: 95%
“…That notwithstanding, we agree with Wang et al . () that it is not easy to differentiate between intention and behaviour during quantitative surveys. For it is assumed that the best predictor of an individual's future behaviour is his/her intention to engage in that behaviour which in turn is influenced by attitudes, subjective norm and perceived behavioural control ( Ajzen, ).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Chau, et al [45] further used discrete choice experiments to examine the attitudes of residents in Hong Kong toward the green attributes of a residential property; they reported that the respondents were willing to pay additional money for energy conservation. To date, TPB has been applied to predict consumers' intention and behavior in a wide range of areas, including environmentally sustainable products [36], electric vehicles [37], green hotels [38,39], and energy conservations [40,41]. This theory is a powerful model in explaining environmentally friendly behavior [42].…”
Section: Practitioners' Attitude Towards Behaviormentioning
confidence: 99%
“…The more positive the individual attitude, the more support from relevant persons as well as the more perceived autonomic control, the higher behavioral intention of the person [33]. To date, TPB has been applied to predict consumers' intention and behavior in a wide range of areas, including environmentally sustainable products [36], electric vehicles [37], green hotels [38,39], and energy conservations [40,41]. This theory is a powerful model in explaining environmentally friendly behavior [42].…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%